1974
DOI: 10.1111/j.1432-1033.1974.tb03624.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fatty‐Acid and Phenol Synthesis in Aspergillus fumigatus

Abstract: Investigations have been conducted into the relationship between fatty acid and phenol synthesis in submerged cultures of Aspergillus fumigatus. Both groups of metabolites are derived from acetate but phenol synthesis only occurs a t a late stage in the incubation period and is dependent on a change in the internal environment of the mycelium. Secretion of acetate-derived phenols commenced many hours after exhaustion of ammonium ions from the culture medium, or transfer of mycelium to glucose solution. Lipid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
(24 reference statements)
2
26
0
Order By: Relevance
“…This condition would allow for the conversion of excess sugar into TAG, and indicates that the nitrogen content of the medium plays an important role in its accumulation. This aspect of metabolism resembles the synthesis of TAG in certain fungi and oleaginous yeasts (Ward & Packter, 1974;Ratledge, 1976 ;Holdsworth & Ratledge, 1988) and other storage polymers such as glycogen (Preiss & Romeo, 1989) and polyhydroxybutyrate (Dawes & Senior, 1973) in bacteria. However, TAG has not been considered a storage product in prokaryotes (Lennarz, 1966 ;Shaw, 1974), but Streptomyces do differ from many other bacteria in a number of features, not least in their filamentous nature and their ability to sporulate and to produce a wide range of antibiotics.…”
Section: Discussionmentioning
confidence: 98%
“…This condition would allow for the conversion of excess sugar into TAG, and indicates that the nitrogen content of the medium plays an important role in its accumulation. This aspect of metabolism resembles the synthesis of TAG in certain fungi and oleaginous yeasts (Ward & Packter, 1974;Ratledge, 1976 ;Holdsworth & Ratledge, 1988) and other storage polymers such as glycogen (Preiss & Romeo, 1989) and polyhydroxybutyrate (Dawes & Senior, 1973) in bacteria. However, TAG has not been considered a storage product in prokaryotes (Lennarz, 1966 ;Shaw, 1974), but Streptomyces do differ from many other bacteria in a number of features, not least in their filamentous nature and their ability to sporulate and to produce a wide range of antibiotics.…”
Section: Discussionmentioning
confidence: 98%
“…The inhibitory actions of tunicamycin and bacitracin suggest that the lipid carrier might be a polyisoprenyl phosphate. and all other substrates were prepared as before [6,9]. Reaction mixtures contained in a final volnme of 0.2 ml: 50 mM Tris/HCl, pH 8.0,20 mM MgCla, 1 mM 2-mercaptoethanol, 100 mM NH,Cl, 15 mM ATP, 2.5 mM glycine and wall-plus-membrane preparation (0.1 ml, protein concentration 3-8 mg/ml).…”
Section: Introductionmentioning
confidence: 99%
“…Paper chromatography was in solvent A, isobutyric acid: 0.5 M ammonia (5:3 v/v). All determinations of radioactivity and analytical methods were as previously described [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have described the inhibition of the formation of antibiotics by ammonium ions and by rapidly utilized nitrogen sources (1,3,4,9,11,12,14). Although the exact biochemical basis of the inhibition is not available, the phenomenon is called nitrogen catabolite regulation by analogy with carbon catabolite regulation, in which carbon catabolites are known to inhibit antibiotic formation (2).…”
mentioning
confidence: 99%
“…The time course study of the ammonia content in the presence of magnesium phosphate (Fig. 3B) revealed that (3), cephamycin (1), novobiocin (11), candihexin (4), fusidic acid (9), or trihydroxytoluene (14), was suggested to be subject to nitrogen catabolite regulation, and the production of oleandomycin, a macrolide antibiotic, was shown to be inhibited by high concentrations of ammonium ions (12), but the exact mechanism of the inhibition is not known. The production of leucomycin by S. kitasatoensis studied here was similarly inhibited in the pres- It is reasonable to suppose that the nitrogen catabolite regulation is reduced under a low ammonium ion concentration created by magnesium phosphate.…”
mentioning
confidence: 99%